PETA DAN ORIENTASI PENELITIAN: Penelitian Berbasis Pengabdian Masyarakat pada Pusat Penelitian dan Penerbitan LPPM UIN Sunan Kalijaga Yogyakarta Tahun 2013–2019 - Muh. Isnanto (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
The development of research in higher education for academic improvement and knowledge development as well as for the professionalism of lecturers is a necessity, as is research based on community service. Therefore, a map and orientation for community service-based research is needed at the Research and Publishing Center of the Institute for Research and Community Service (LPPM) UIN Sunan Kalijaga. The results of the research show firstly, the research map at the LPPM Research and Publishing Center has experienced a shift in terms of quantity, clusters, research output, and research that has been carried out by lecturers/research researchers if they need credit numbers, now there is awareness and this has changed to become an academic need for lecturers /researcher. Second, the research orientation is that research results are required to be published in the OJS journal and research based on community service at the Research and Publishing Center started in 2018. Third, the research results have been used as a reference for preparing Semester Learning Plans (RPS) for courses, namely 80%, and not used as a reference of 20%.